O epidítico como recurso para a representação dos contemporâneos na epistolografia de Plínio, o Jovem - Giesen, Kátia Regina (2016)
Originally a communicational, ordinary and private genre, epistolography became an object of literary appreciation in the hands of Pliny the Younger, who, by organizing texts written by him to friends and publishing them in a collection, used his letters as a tool to create pictures of himself and of public and private life during the late first century and early II AD. Among the more than two hundred letters that comprise books I to IX of Pliny"s correspondence, there are several texts whose main subject is portraying men and women of his times. In such cases, the author employs expedients of epideictic oratory to elaborate images of his contemporaries. In this context, the letters in which praise is addressed to still living contemporaries of Pliny stand out, since that kind of attitude was not, according to Cicero (De or. II, 341-342), seen under positive light in Roman context. Analyzing the epistolary genre from a literary perspective, we aim at demonstrating how and with what functions Pliny used epideictic speech instruments in the text of the thirteen letters in which there are praises to men who are alive and still active in the society of the time. To do so, we used elements from Discourse Analysis as presented by Maingueneau; the concept of representation set by Roger Chartier; and ancient theorization about epistolography and epideictic genre. As results, we propose that the praise offered in Pliny"s laudatory letters feature images of exemplary individuals, both because of their moral virtues and due to their involvement with the literary culture of their time, whether by acting on philosophical, oratorical or poetic practice. These textual images set the tone of Pliny"s optimism in relation to his contemporary times, which plays an important part in his role as a supporter of Trajan's government.